2013
DOI: 10.1111/j.1600-048x.2013.05846.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource allocation between growth and endothermy allows rapid nestling development at low feeding rates in a species under high nest predation

Abstract: Nestling development is among the most energy‐demanding periods of a bird’s lifetime and altricial species require extensive parental energy investment in the form of feeding and heating. In the present study I analyze the relation and trade‐offs between nestling growth, development of thermoregulation and feeding rate in blackcap Sylvia atricapilla, a species suffering from high nest predation. Nestlings were characterized by rapid growth but they achieved only 80% of adult mass prior to fledging. Body mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
61
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 42 publications
5
61
0
1
Order By: Relevance
“…O'Connor, 1975;Olson, 1992;Visser and Ricklefs, 1993;Pereyra and Morton, 2001;Brown and Downs, 2002;Cheng and Martin, 2012;Wegrzyn, 2013). This trade-off is corroborated by the difference in the ontogeny of endothermic heat production between altricial and precocial chicks: precocial chicks are more mature and have greater thermogenic capacity at hatching, but a slower growth rate compared with altricial nestlings (Ricklefs et al, 1998).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…O'Connor, 1975;Olson, 1992;Visser and Ricklefs, 1993;Pereyra and Morton, 2001;Brown and Downs, 2002;Cheng and Martin, 2012;Wegrzyn, 2013). This trade-off is corroborated by the difference in the ontogeny of endothermic heat production between altricial and precocial chicks: precocial chicks are more mature and have greater thermogenic capacity at hatching, but a slower growth rate compared with altricial nestlings (Ricklefs et al, 1998).…”
Section: Introductionmentioning
confidence: 74%
“…However, nestlings of altricial species are poikilothermic and have little or no capacity to maintain core body temperature when exposed to temperatures below the thermal neutral zone (TNZ; where the heat produced by basal metabolism is enough to maintain a normothermic body temperature) during the first part of their life Baarendse et al, 2007). A relatively narrow TNZ develops during the first few days post-hatching, but nestlings still decrease metabolic rate and body temperature when exposed to temperatures below thermal neutrality , during which time nestlings are exclusively dependent on parental heat for maintaining body temperature (Ricklefs, 1984;Wegrzyn, 2013). It is not until several days later that they are able to increase metabolic rate in response to sub-neutral temperatures (O'Connor, 1975;.…”
Section: Introductionmentioning
confidence: 99%
“…Por lo anterior, se ha propuesto que la aparente incapacidad de los polluelos altriciales para producir calor endó-geno (i.e. ectotermos) durante los primeros días después de la eclosión e incluso que retrasen la endotermia, es en realidad una estrategia que les permite invertir todos sus recursos en desarrollarse y cargar el gasto de su estabilidad térmica a los padres (Clavijo-Baque y Bozinovic 2012, Wegrzyn 2013).…”
Section: Introductionunclassified
“…Another potential cost of begging may be the risk of nest predation induced by begging vocalization that may inadvertently attract the attention of predators. Nest predation is a major source of reproductive failure in birds (Martin , ) and thus it can exert selective pressure on proximate and evolutionary solutions in offspring strategies (Martin , , , Wiklund , Węgrzyn ). Indeed, there is broad evidence that begging calls increase nest predation (Haskell , , Dearborn , McDonald et al .…”
mentioning
confidence: 99%
“…A recent study reported that Blackcap nestlings exhibit a series of solutions to enhance their chance of survival in such a risky environment (Węgrzyn ). They grow fast under minimum feeding rates and are able to fledge at only 80% of adult mass, minimizing exposure time to predators.…”
mentioning
confidence: 99%